Biotransformation of gabapentin in surface water matrices under different redox conditions and the occurrence of one major TP in the aquatic environment. (15th June 2018) - Henning, Nina; Kunkel, Uwe; Wick, Arne; Ternes, Thomas A.
Abstract: Laboratory-scale incubation experiments in water/sediment systems were conducted to test the transformation behavior of the anticonvulsant gabapentin (GBP) under different environmental conditions (aerobic, anaerobic, with abiotic controls). GBP was transformed by biological processes as it was eliminated quickly under aerobic conditions (dissipation time 50% of initial concentration (DT50 ): 2–7 days) whereas no decrease was observed under anaerobic conditions. Measurements via high resolution mass spectrometry (LC-Orbitrap-MS) revealed eight biological transformation products (TPs). Three of them were identified with reference standards (GBP-Lactam, TP186, TP213), while for the other five TPs tentative structures were proposed from information by MS 2 /MS 3 experiments. Furthermore, the quantitatively most relevant TP GBP-Lactam was formed via intramolecular amidation (up to 18% of initial GBP concentration). Incubation experiments with GBP-Lactam revealed a higher stability against biotic degradation (DT50 : 12 days) in contrast to GBP, while it was stable under anaerobic and abiotic conditions. Besides GBP, GBP-Lactam was detected in surface water in the μg L −1 range. Finally, GBP and GBP-Lactam were found in potable water with concentrations up to 0.64 and 0.07 μg L −1, respectively. According to the elevated environmental persistence of GBP-Lactam compared to GBP and its presumed enhanced toxicity, we recommend to involve GBP-Lactam into monitoring programs. Graphical abstract: Highlights: In water/sediment systems Gabapentin was biodegraded under aerobic conditions and was persistent under anaerobic conditions. The transformation pathway of Gabapentin could be elucidated. Gabapentin and gabapentin-Lactam were detected in surface water, ground water and drinking water.